(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to find out the implementation of the policy on handling Covid 19 in Sea Tumpengan Village, Pineleng District, Minahasa Regency in the study of public administration science. The type of research used in this study is a qualitative approach with descriptive analysis. The selection of a qualitative approach to answer the research problem proposed by emphasizing on interpretation, not on generalization and more on revealing the meaning and understanding of the phenomenon of implementing the policy for handling Covid 19 in Sea Tumpengan Village, Pineleng District, Minahasa Regency . Data collection techniques used include documentation, observation and interviews. Qualitative data analysis techniques used in this study refer to the analysis techniques proposed by Miles and Huberman, namely data reduction, data presentation, drawing conclusions or verification. It can be concluded that the implementation of the Covid-19 handling policy in Sea Tumpengan Village, Pineleng District, Minahasa Regency is seen from the environmental conditions, the relationship between organizations, the budget that comes from village funds and the facilities used by the implementing team and direct assistance by the community to meet the needs of the implementing team make the implementation of the policy to handle Covid 19 run well. Kata Kunci : Implementation, Policy, Handling, Covid-19